EFL teachers’ challenges in promoting learner autonomy in the 21st-century learning - Putu Wiraningsih; Made Hery Santosa (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2020)
Teachers have a responsibility to help students become autonomous learners. However, in promoting learner autonomy, the teachers were faced with the challenges. This descriptive qualitative study aimed to describe the challenges in promoting learner autonomy in 21st-century learning faced by EFL teachers and their strategies. The data were collected through a semi-structured interview technique. Four qualified EFL junior high school teachers with at least five years of teaching experience in Singaraja Bali Indonesia were involved. The interview guideline was constructed based on the dimensions of policy constraints, institutional constraints, language teaching methodology, and learner's background. The interviews were transcribed and categorized into the table of identification based on the four dimensions. Finally, the data regarding the challenges and the strategies were interpreted, and the excerpts of the interview were provided. The results show that the policy constraint identified in this study was due to the school zoning system. The institutional constraint was due to the unscheduled events. The language teaching methodology was due to the lack of knowledge of teaching strategy and different characteristics of students. Thus, in transforming the challenges into possibilities, some strategies were implemented, such as initiating activities, applying collaborative learning, and having good planning and time management.